A survey of Brignoliolus Ovchinnikov, 1999 stat. rev. (Araneae, Agelenidae) with the description of a new species from Israel - Zonstein, Sergei; Marusik, Yuri M. (Zootaxa, 2024)
Brignoliolus Ovchinnikov, 1999 stat. rev. originally described as a subgenus of Coelotes Blackwall, 1841 is rediagnosed, redescribed and elevated to the genus rank. This genus is distinguished from Coelotes by a lighter general colouration and a longer and thinner apical segment of the posterior lateral spinnerets, as well as by the distinctive shape of the epigyne with long teeth located anteriorly of a trapezoidal or sandglass fovea. Brignoliolus is considered to encompass nine species, including B. ovchinnikovi sp. nov. from Israel, described herein. The new species most resembles B. vignai and B. caudata but differs from them by the shape and spination of cymbial tip and relative length of epigynal fovea and teeth. All species are discussed, diagnosed and their correct distributional data is provided. Eight new combinations are established: B. arganoi (Brignoli, 1978) comb. nov.; B. caudatus (de Blauwe, 1973) comb. nov.; B. charitonovi (Spassky, 1939) comb. nov.; B. coenobita (Brignoli, 1978) comb. nov.; B. juglandicola (Ovchinnikov, 1984) comb. nov.; B. nenilini (Ovchinnikov, 1999) comb. nov.; B. turkestanicus (Ovchinnikov, 1999) comb. nov.; B. vignai (Brignoli, 1978) comb. nov..